(untitled) (Research, Society and Development, 2025)
The Mandibular Canal (MC) is located inside the body of the mandible, extending from the mandibular foramen to the mental foramen, and it may follow as a single canal or present anatomical variations. The most common variations described in the literature include retromolar canals, bifid mandibular canals (BMCs), and trifid mandibular canals (TMCs). This study aims to identify and highlight these anatomical variations, emphasizing their importance for diagnosis in panoramic radiographs and their relevance for clinical practice. A literature review was conducted using the Pubmed, Bireme, Lilacs, and Scielo databases with descriptors in Health Sciences: Mandibular Canal, Anatomical Variation, and Panoramic Radiograph, covering the period from June 2020 to July 2021. Panoramic radiography is a widely used imaging modality by dentists due to its ability to provide a comprehensive view of the maxilla, mandible, and adjacent structures, in addition to being easily accessible. However, the literature indicates that exclusive use of this examination may underestimate important details of the MC anatomical variations. Therefore, cone beam computed tomography (CBCT) is recommended as a complementary exam for greater diagnostic precision. The results emphasize the importance of recognizing the anatomical variations of the MC, with a focus on BMCs. Knowledge of these variations by clinicians is essential to adapt the planning and execution of procedures, aiming to prevent complications such as: postoperative neuro-sensory deficits due to anesthetic failures; surgical complications in implant insertion and third molar removal; inadequate planning of removable prostheses in atrophied mandibles; and risks in osteotomies involving the mandibular region.